2021
DOI: 10.1111/nph.17888
|View full text |Cite
|
Sign up to set email alerts
|

Canopy damage during a natural drought depends on species identity, physiology and stand composition

Abstract: Summary Vulnerability to xylem cavitation is a strong predictor of drought‐induced damage in forest communities. However, biotic features of the community itself can influence water availability at the individual tree‐level, thereby modifying patterns of drought damage. Using an experimental forest in Tasmania, Australia, we determined the vulnerability to cavitation (leaf P50) of four tree species and assessed the drought‐induced canopy damage of 2944 6‐yr‐old trees after an extreme natural drought episode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 85 publications
(125 reference statements)
0
13
3
Order By: Relevance
“…Biotic habitat factors such as differences in the associated enemy and plant community may also alter the effects of climate-driven selection on a focal species [ 93 , 94 ]. In Tasmanian eucalypts, for example, the potential for co-occurring rainforest species to affect clines in foliar glaucousness was noted early [ 50 ], and a recent study showed that drought damage in two focal eucalypt species is differentially influenced by neighbouring tree species [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biotic habitat factors such as differences in the associated enemy and plant community may also alter the effects of climate-driven selection on a focal species [ 93 , 94 ]. In Tasmanian eucalypts, for example, the potential for co-occurring rainforest species to affect clines in foliar glaucousness was noted early [ 50 ], and a recent study showed that drought damage in two focal eucalypt species is differentially influenced by neighbouring tree species [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…wind, and water stress) ( Gora and Esquivel-Muelbert, 2021 ). For example, greater drought damage in faster growing individuals has been reported in tree species ( Martínez-Vilalta et al., 2012 ; Zang et al., 2014 ), including eucalypts ( Ammitzboll et al., 2020 ) (but see Britton et al., 2022 ), and may be due to physiological trade-offs or greater depletion of soil water reserves ( White et al., 2009 ; Wright et al., 2010 ; Gleason et al., 2016 ; Brodribb et al., 2020 ). In the present case, despite the above-average maximum temperatures experienced during the growing period ( Costa e Silva et al., 2019 ), the field trial studied was not subject to a major experiment-wide abiotic stress event, and mortality gradually accumulated consistent with biotic causes, including inter-tree competition.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, despite the above-average maximum temperatures experienced during the growing period ( Costa e Silva et al., 2019 ), the field trial studied was not subject to a major experiment-wide abiotic stress event, and mortality gradually accumulated consistent with biotic causes, including inter-tree competition. However, empirical studies indicate that the various biotic and abiotic causes of mortality may not be independent ( Camarero et al., 2016 ; Gleason et al., 2017 ; Britton et al., 2022 ). Thus, the changing patterns of size-dependent mortality with age may be complex and even species-specific ( Bigler and Veblen, 2009 ; Wright et al., 2010 ; Britton et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prolonged drought conditions might ultimately lead to hydraulic failure because of continuous residual water loss via the cuticle and bark [7]. Under severe and prolonged water stress, xylem tensions therefore ultimately reach critical thresholds causing water-filled vessels to embolize, which disrupts the continuous water column and ultimately causes plant death [8][9][10]. Thus, the likelihood of hydraulic failure and xylem characteristics are supposed to be highly interconnected.…”
Section: Introductionmentioning
confidence: 99%